Teletraffic Engineering in UMTS FDD Mode Networks - Caramês Garcia, Miguel (2001)
This paper presents a tool for multi-service traffic engineering in UMTS FDD mode. For each of the WCDMA system scenarios, the power restrictions and a given mixture of symmetric applications are considered. The maximum number of supported codes was obtained by previous simulations, taking into account carrier-to-interference constraints, leading to a given available data rate per cell. Given the spread-factor, with the basic resource being considered of 15 kb/s, the various applications request a certain number of basic code channels. A standard algorithm was used to compute each application’s blocking probability, Pb, as a function of the fraction of active users in cells. In the urban1 scenario (20 % data at 40 kb/s plus 80% voice), using one carrier per cell, UMTS can support 26 speech users plus 7 data users for Pb = 2 %. If two carriers were used, it would support 60 speech users and 14 data users. In the urban2 scenario, as data at 320 kb/s is considered, system performance degrades, which can only be overcome by using three carriers per cells, which seems impracticable in an actual system. The consideration of terminal mobility leads to a slight decrease on the number of supported users.